Analisis Program Perjusa dalam Meningkatkan Mutu Pai di MTS Muhammadiyah 15 Medan - Pratama, Aris Firjatullah; Zuliana, Zuliana (Al-Ulum: Jurnal Pendidikan Islam, 2024)
The aim of this research is to find out about the perjusa program in improving the quality of Islamic religious education at MTS Muhammadiyah 15 Medan. The program is one component to support the quality of education, especially in schools. This research uses qualitative methods with the type of field research. This research is supported by significant data collection techniques, namely by observing and interviewing students and teachers as data sources/primary informants. Meanwhile, in data analysis, the author carried out data collection, data reduction, and presented the data in the form of a short description. The results of this research show that in improving the quality of Islamic religious education, the Perjusa program carries out several activities including: 1). Conducting science seminars, 2). Performing evening worship, 3). Take a relaxing walk with the people.